TGF-β1 genotype and accelerated decline in lung function of patients with cystic fibrosis. Issue 6 (1st June 2000) - Arkwright, Peter D; Laurie, Steven; Super, Maurice; Pravica, Vera; Schwarz, Martin J; Webb, A Kevin; Hutchinson, Ian V
Abstract : BACKGROUND: Polymorphisms in transforming growth factor (TGF)-β1 associated with variations in cytokine levels are linked to fibrosis in a number of tissues. However, the contribution of this cytokine to organ fibrosis in patients with cystic fibrosis is presently unclear. This study was undertaken to examine the association between TGF-β1 gene polymorphisms and the development of pulmonary dysfunction in patients with cystic fibrosis. METHODS: Polymorphisms in the TGF-β1 gene defining amino acids of codons 10 and 25 were determined by ARMS-PCR using DNA stored on 171 Caucasian patients who were homozygous for the ΔF508 mutation of the cystic fibrosis transmembrane conductance regulator (CFTR) gene. Clinical information on the patients was obtained from medical records. RESULTS: Patients with cystic fibrosis of a TGF-β1 high producer genotype for codon 10 had more rapid deterioration in lung function than those with a TGF-β1 low producer genotype. The relative risk of accelerated decline in forced expiratory volume in one second (FEV1 ) to 50% predicted and forced vital capacity (FVC) to 70% predicted of patients with a high producer genotype was 1.74 (95% CI 1.11 to 2.73) compared with 1.95 (95% CI 1.24 to 3.06) for those with a low producer genotype. DISCUSSION: TGF-β1 genotypes may have a role in mediating pulmonary dysfunction in patients with cystic fibrosis. Further work is required to determine whether inhibition of TGF-β1 activity in these patients may slow disease progression.